Determination of Minimum Clinically Important Difference (MCID) in Visual Analog Scale (VAS) Pain and Foot and Ankle Ability Measure (FAAM) Scores After Hallux Valgus Surgery. (June 2019) - Sutton, Ryan M.; McDonald, Elizabeth L.; Shakked, Rachel J.; Fuchs, Daniel; Raikin, Steven M.
Background: Minimum clinically important difference (MCID) defines a threshold when determining clinically significant treatment improvement. Visual analog scale (VAS) and Foot and Ankle Ability Measure activities of daily living (FAAM-ADL) are commonly used for measuring hallux valgus correction. This study aimed to determine MCID in VAS pain and FAAM-ADL scores for hallux valgus correction and additionally, to identify variables influencing achievement of the VAS pain MCID. Methods: Patients undergoing hallux valgus surgery were retrospectively included. VAS pain, FAAM-ADL, and pain satisfaction surveys were collected preoperatively and minimum 1-year postoperatively. Using a 6-point Likert-type pain satisfaction scale, patients reporting low postoperative satisfaction scores 1 through 3 were categorized as "dissatisfied, " and high satisfaction scores 4 through six as "satisfied." One distribution-based method and 2 anchor-based methods were used to calculate MCID. Further, a logistic regression was calculated to determine if one group (defined by sex, pain satisfaction, preoperative VAS pain, concomitant lesser toe deformity correction, and specific hallux valgus correction procedure) had a greater likelihood of achieving the VAS pain MCID threshold. This study included 170 patients with postoperative follow-up averaging 23.6 months. Results: Calculated MCID scores ranged from 1.8 to 5.2 points for VAS pain and 11.1 to 22.7 points for FAAM-ADL. Moderate deformity correction with proximal first metatarsal osteotomy (Ludloff) (OR=2.236, P = .036) or severe deformity correction with first tarsometatarsal arthrodesis (Lapidus) (OR=3.145, P = .046); and higher preoperative pain scores (OR=1.045, P < .010) had significantly higher odds of meeting VAS pain MCID. Conclusion: This study demonstrated MCID values that may indicate significant pain and function improvement after hallux valgus correction. Higher preoperative pain, and utilization of proximal metatarsal osteotomy or first tarsometatarsal arthrodesis for moderate or severe deformity correction resulted in significantly greater likelihood of reaching the VAS pain MCID than utilizing distal metatarsal and/or proximal phalanx osteotomy for mild deformity treatment. Level of Evidence: Level IV, validating outcome measures.